(untitled) (Annals of Medical Research, 2025)
Aim: Insulin resistance (IR) is a crucial characteristic of type 2 diabetes mellitus (T2DM) and can also occur independently or in other conditions such as obesity and metabolic syndrome. Oxidative stress significantly contributes to IR pathology. Ischemia-modified albumin (IMA) is a biomarker of oxidative stress and has been studied for its potential link to IR. This study aimed to identify the relationship between IMA levels and IR. Materials and Methods: We conducted a prospective study involving 101 IR patients without diabetes mellitus and 101 healthy controls. HOMA-IR was used to classify IR and control groups. IMA levels were measured using a colorimetric method. The groups’ IMA values were compared, and correlations between IMA and other parameters were determined. Results: There was no statistically remarkable difference in IMA levels between the IR and control groups (p=0.27). In addition, no significant correlation was observed between IMA and HOMA-IR (p=0.60). Significant differences were found in glucose, insulin, and HOMA-IR levels between the IR and control groups (p<0.001 for insulin and HOMA-IR, p<0.01 for glucose). Conclusion: Despite higher IMA levels in the IR group, the difference was not statistically notable, and no significant correlation with HOMA-IR was found. This may be due to the finite number of patients with high HOMA values, the need for more precise data on body mass index, and longer follow-up. Further prospective studies are necessssary to define the connection between IMA and IR.